Why do we need a general agreement on movements of people (GAMP)? - Thomas Straubhaar (Hamburg Institute of International Economics (HWWA), 2000)
This paper argues that global games need global rules. Times of globalisation call for an international framework to regulate efficiently international movements of people. More than ever before, migration is a global phenomenon. This paper discusses the economic necessity of a shift from national migration policies to an international regime. My suggestions go into the direction of a GAMP - a General Agreement on Movements of People. This labour market analogy to the GATT (WTO) and GATS is intended to provide an international regime for the movement of people across national borders. It proceeds from the conviction that in general the free international movement of people - like the free movement of goods and capital - is beneficial to all parties involved (i.e. the migrants, the country of origin and the country of destination). Consequently, it aims first and foremost at a liberalisation of the movement of people and for general acceptance of the free entry and exit of migrants. However, it should also provide an instrument for internalising externalities provoked by international migration. To avoid brain drain effects in the sending areas and congestion effects in the receiving areas it might be wise to impose a migration fee that makes exit and entry more expensive. – – Während GATT und GATS und damit die WTO den Welthandel regulieren, und es für den internationalen Geld- und Kapitalverkehr Institutionen wie die BIZ, den IMF oder die Weltbank gibt, fehlt für den Bereich der internationalen Migration eine analoge internationale Behörde (diese Lücke vermögen auch die ILO und die IOM nicht zu füllen). Dieses Diskussionspapier deckt die ökonomische Notwendigkeit für ein GAMP (General Agreement on Movements of People) auf und skizziert dessen Inhalte. GAMP wird von der Überzeugung geleitet, dass die internationale Freizügigkeit für Arbeitskräfte genauso vorteilhaft ist wie der internationale Freihandel für Güter. Andererseits entstehen mit der internationalen Migration externe Effekte in Form eines Brain Drains im Herkunftsland und in Form von Ballungs- und Verdrängungseffekten im Aufnahmeland. Um diese negativen Auswirkungen zu internalisieren, wird vorgeschlagen, eine zweckgebundene Migrationsabgabe zu erheben.
Keywords: 330; Internationale Arbeitsmobilität; WTO-Regeln; Internalisierung externer Effekte; Brain Drain; Agglomerationseffekt; Welt